Analysis of Positive Weak Solutions for a Class of Fractional Laplacian Elliptic Systems of Type Kirchhoff - Guefaifia R.; Allahem A.; Jan R.; Boulaaras S.; Biomy M. (Institute for Ionics, 2025)
In this research work, a sub-supersolution approach is utilized to investigate the existence and nonexistence of weak positive solution for a class of fractional Laplacian Kirchhoff type elliptic systems in bounded domains with one parameter. ? 2024, The Author(s).